Role of Heat Shock Protein 70 in Innate Alloimmunity - Land, Walter G. (Frontiers in Immunology, 2012)
This article briefly describes our own experience with the proven demonstration of heat shock protein 70 (HSP70) in reperfused renal allografts from brain-dead donors and reflects about its potential role as a typical damage-associated molecular pattern (DAMP) in the setting of innate alloimmunity. In fact, our group was able to demonstrate a dramatic up-regulation of HSP70 expression after postischemic reperfusion of renal allografts. Of note, up-regulation of this stress protein expression, although to a lesser extent, was already observed after cold storage of the organ indicating that this molecule is already induced in the stressed organism of a brain-dead donor. However, whether or not the dramatic up-regulation of HSP70 expression contributes to mounting an innate alloimmune response cannot be judged in view of these clinical findings. Nevertheless, HSP70, since generated in association with postischemic reperfusion-induced allograft injury, can be called a typical DAMP – as can every molecule be termed a DAMP that is generated in association with any stressful tissue injury regardless of its final positive or negative regulatory function within the innate immune response elicited by it. In fact, as we discuss in this article, the context-dependent, even contradistinctive activities of HSP70 reflect the biological phenomenon that, throughout evolution, mammals have developed an elaborate network of positive and negative regulatory mechanisms, which provide balance between defensive and protective measures against unwarranted destruction of the host. In this sense, up-regulated expression of HSP70 in an injured allograft might reflect a pure protective response against the severe oxidative injury of a reperfused donor organ. On the other hand, up-regulated expression of this stress protein in an injured allograft might reflect a (futile) attempt of the innate immune system to restore homeostasis with the aim to eliminate the “unwanted foreign allograft invader” by contributing to development of an adaptive alloimmune response. However, this adaptive immune response against donor histocompatibility alloantigens – in its evolutionary sense aimed to restore homeostasis – is by no means protective from a recipient’s view point but tragically ends up with allograft rejection. Indeed: in this sense, allograft rejection is the result of a fateful confusion by the immune system of danger and benefit!